Chemical Constituents of Phyllanthus acidus (L.) Skeels - Alimboyoguen, Agnes B; Castro-Cruz, Kathlia A De; Fidel, Evangelina M; Shen, Chien-Chang; Tsai, Po-Wei (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: This study describes the isolation of chemical constituents from the leaves and bark of Phyllanthus acidus, a medicinal plant widely used for the treatment of several ailments. Materials and Methods: The crude extract of P. acidus was chromatographed on a gravity column dry packed with silica gel and was fractionated by increasing proportions of acetone in CH2Cl2. The purified isolates were subjected to NMR for structure elucidation. Their structures were identified mainly by using 1H-NMR and by comparing current NMR data with those reported in the literature. Results: The results showed that the air-dried leaves extracts of the plant afforded mixture of β-sitosterol and stigmasterol while the bark yielded mixture of phyllanthol, α-amyrin, β-amyrin and lupeol. Conclusion: The air-dried of DCM extract of P. acidus resulted in the isolation of the mixture of phyllanthol, α- amyrin, β-amyrin and lupeol from the bark and mixture of β-sitosterol and stigmasterol from the leaves of the plant. It is important to conduct detailed pharmacological and toxicity investigations as well as clinical studies using different doses or concentrations to verify its traditional uses.
Keywords: Phyllanthus acidus; Karamay; Phyllanthol; Lupeol; Amyrin; Sitosterol; Stigmasterol